2021
DOI: 10.19101/ijatee.2021.874586
|View full text |Cite
|
Sign up to set email alerts
|

An application of logistic model tree (LMT) algorithm to ameliorate Prediction accuracy of meteorological data

Abstract: Weather forecasting is considered as one of the approaches which are used to check the state of the atmosphere in the future at a specified location. A type of weather forecasting called as rainfall prediction has the highest influence in the farming & agricultural sector and other various sectors like natural disaster management etc. Accurate and timely rainfall prediction is one of the important factors in today's environment. Since the rainfall parameters keep on changing around the world in different place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Algorithm 2: Snapshot of M5 model tree approach with prune & Error function Fayaz et al [14] provided a stepwise mathematical implementation of the logistic model tree (LMT), and the data for this study was acquired from the Indian Metrological Department (IMD) in Pune from 2012 to 2017, and it contains roughly 5580 records. Five factors make up the data, including humidity and temperature as independent variables and rainfall as the objective variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algorithm 2: Snapshot of M5 model tree approach with prune & Error function Fayaz et al [14] provided a stepwise mathematical implementation of the logistic model tree (LMT), and the data for this study was acquired from the Indian Metrological Department (IMD) in Pune from 2012 to 2017, and it contains roughly 5580 records. Five factors make up the data, including humidity and temperature as independent variables and rainfall as the objective variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other Elements: The research identified a number of other factors like learning environment, family issues and instabilities, parental habits and peer relationships that were good predictors of student performance. These included a student's success in online coursework and the ratio of credits attempted to credits finished [30][31][32][33].…”
Section: Student Performance: Analysis Of the Futurementioning
confidence: 99%
“…One common method for addressing data heterogeneity problems is to transform and combine them into a single data source [7][8][9][10]. Lexical, syntactic, and geometrical inconsistencies that arise during data integration may cause some information to be lost when all of the data sources are integrated into one source, increasing the storage capacity requirement to that of a data warehouse.…”
Section: Review Of Literaturementioning
confidence: 99%